Orthogonal time frequency space multiple access using index modulation - Doğan Tusha, Seda; Tusha, Armed; Althunibat, Saud; Qaraqe, Khalid (Institute of Electrical and Electronics Engineers Inc., 2023)
Orthogonal time frequency space (OTFS) is a recent two-dimensional modulation technique utilizing delay-Doppler domain and nominated as a promising candidate waveform for beyond 5G communication systems. By leveraging both time and frequency selectivity of doubly-dispersive radio channels, it has shown a better performance compared to traditional schemes. OTFS offers different options for accommodating multiple users on a given resource block. This article introduces a novel OTFS based uplink multiple access scheme by means of index modulation (IM) in delay-Doppler domain. IM based OTFS multiple access (OTFS-IMMA) proposes the coexistence of multiple users over the same delay-Doppler resources. Unlike conventional OTFS multiple access schemes, OTFS-IMMA allows users to employ IM to activate a subset of the available delay-Doppler resources without a coordination by the base station. Although data collision may occur between the users, our analysis shows that the achievable performance is still better than other schemes. Moreover, the proposed OTFS-IMMA scheme paves the way for flexible resource utilization in OTFS-MA to satisfy various users' demands in beyond 5G systems. It has been shown via both mathematical analysis and simulations that the proposed OTFS-IMMA scheme offers significant enhancement not only on bit error rate performance but also on the overall system efficiency. In addition, the achieved performance gain through OTFS-IMMA further increases as the number of channel taps and/or the number of delay-Doppler bins increase.
Keywords: OTFS; Multiple Access; Index Modulation (IM); Doubly-Dispersive Channel; Maximum Likelihood (ML) Detector